PKM. PENGEMBANGAN SOFT DAN HARD SKILL BERBASIS TRI HITA KARANA DALAM MEMPERSIAPKAN DIRI UNTUK MAMPU BERSAING DI ERA 5.0 - Desak Gede Dika Pradnyani Dewi; I Made Surat (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
Era 5.0 or Super Smart Society (society 5.0) was introduced by the Japanese Government in 2019. After entering the era of the industrial revolution, Indonesia will enter the era of society 5.0. There are three main abilities in dealing with society 5.0, namely the ability to solve complex problems and become a problem solver for oneself and also many people, the ability to think critically in everyday life in the environment and society. Society 5.0 can be interpreted as the integrity of virtual and physical space, so that everything becomes easy. In welcoming the era of society 5.0, education plays an important role in producing human resources (HR). Apart from education, there are several elements that have a role to support, such as the government, community organizations (ormas) and the entire community also taking part in welcoming the upcoming era of society 5.0. In this case, we as students also need to have the readiness and ability to think Higher Order Thinking Skills (HOTS), develop soft and hard skills to be able to answer the global challenges of the era of society 5.0. This is done to minimize the gap in the mindset and technology of each individual. In the era of society 5.0, humans are required to more quickly produce solutions to meet their needs. This has an impact on humans to continue to explore information, as well as create new innovations to support survival.